Optimal monetary policy with durable and non-durable goods - Christopher J. Erceg; Andrew T. Levin (European Central Bank (ECB), 2002)
The durable goods sector is much more interest sensitive than the non-durables sector, and these sectoral differences have important implications for monetary policy. In this paper, we perform VAR analysis of quarterly US data and find that a monetary policy innovation has a peak impact on durable expenditures that is roughly five times as large as its impact on non-durable expenditures. We then proceed to formulate and calibrate a two-sector dynamic general equilibrium model that roughly matches the impulse response functions of the data. While the social welfare function involves sector-specific output gaps and inflation rates, we find that performance of the optimal policy rule can be closely approximated by a very simple rule that targets a weighted average of aggregate wage and price inflation rates. In contrast, some commonly-prescribed policy rules (such as strict5 price inflation targeting and Taylor's rule) perform very poorly in terms of social welfare.
Keywords: E31; E32; E52; 330; Geldpolitik; Dauerhafte Konsumgüter; Konsumgüter; VAR-Modell; Soziale Wohlfahrtsfunktion; Inflationssteuerung; Taylor-Regel; Theorie; USA